ELF3 modulates type II collagen gene (COL2A1) transcription in chondrocytes by inhibiting SOX9-CBP/p300-driven histone acetyltransferase activity. (2nd January 2017) - Otero, Miguel; Peng, Haibing; Hachem, Karim El; Culley, Kirsty L.; Wondimu, Elisabeth B.; Quinn, Justin; Asahara, Hiroshi; Tsuchimochi, Kaneyuki; Hashimoto, Ko; Goldring, Mary B.
ABSTRACT: Aim : We showed previously that E74-like factor 3 (ELF3) protein levels are increased in osteoarthritic (OA) cartilage, that ELF3 accounts for inflammatory cytokine-driven MMP13 gene expression, and that, upon induction by interleukin-1β, ELF3 binds to the COL2A1 promoter and suppresses its activity in chondrocytes. Here, we aimed to further investigate the mechanism/s by which ELF3 represses COL2A1 transcription in chondrocytes. Methods and Results : We report that ELF3 inhibits Sox9-driven COL2A1 promoter activity by interfering with the activator functions of CBP/300 and Sox9. Co-transfection of the pGL2B- COL2A1 (–577/+3428 bp) reporter construct with Sox9 and with Sox5 and/or Sox6 increased COL2A1 promoter activity, and ELF3 overexpression significantly reduced the promoter transactivation. Co-transfection of ELF3 with the pLuc 4x48 enhancer construct, containing the 89-bp COL2A1 promoter and lacking the previously defined ELF3 binding sites, decreased both basal and Sox9-driven promoter activity. Co-transfection of ELF3 with a Gal4 reporter construct also inhibited Gal4-Sox9-driven transactivation, suggesting that ELF3 directly interacts with Sox9. Using truncated Sox9 fragments, we found that ELF3 interacts directly with the HMG domain of Sox9. Importantly, overexpression of ELF3 significantly decreased Sox9/CBP-dependent HAT activity. Finally, we show evidence that increased ELF3 mRNA expression in OA chondrocytes correlates with hypermethylation of the proximal promoter, suggesting that ELF3 transcription is subjected to epigenetic control in OA disease. Conclusion : Our results highlight the contribution of ELF3 to transcriptional regulation of COL2A1 and its potential role in OA disease, and uncover epigenetic mechanisms at play in the regulation of ELF3 and its downstream targets in articular chondrocytes.